Metallophthalocyanine‐enriched Langmuir‐Schaefer multilayers of poly(vinylidene fluoride)‐based nanocomposites. Issue 31 (7th April 2019) - Kumar, Chandan; Viswanath, P.
ABSTRACT: Engineering the surface morphology with optimized crystallinity is very crucial for practical applications such as energy storage, electromechanical devices, and self‐cleaning. Organic nanocomposites permit one to tune the dielectric properties by controlling the crystallinity and surface morphology. Here, we report our investigation on metallophthalocyanines of nickel and copper as an organic additive to poly(vinylidene fluoride) (PVDF) to modify the structural, optical, wetting, and electrical properties of the nanocomposite multilayers deposited using Langmuir‐Schaefer method. The incorporation of the metallophthalocyanines in the nanocomposite multilayers was confirmed from the signature Bragg peaks, and the fingerprint absorbance using grazing incidence X‐ray diffraction and Fourier transform infrared spectroscopy, respectively. Aggregation behavior of the metallophthalocyanines in the polar matrix of PVDF was studied using ultraviolet–visible spectroscopy. Surface morphological studies using field emission scanning electron microscopy on the nanocomposite multilayers show the presence of both spherical crystallites and rod‐like structures which depends upon the composition and nature of metal in metallophthalocyanine. The surface wettability of these multilayers was investigated using static and dynamic contact angle studies. A significant enhancement in the dielectric constant has been observed for both nanocomposites relative to the pristine multilayer of PVDF. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2019, 136, 47818. Abstract : Nanocomposite multilayers of poly(vinylidene fluoride) (PVDF) with metallophthalocyanine of nickel and copper were deposited using Langmuir‐Schaefer method. The structural, crystallinity, morphology, and wetting behavior of the multilayer were investigated using GIXD, FTIR, FESEM, and contact angle meter, respectively. A maximum crystallinity of about 97% was estimated for both the nanocomposites with different surface morphology and wetting properties. Nanocomposite multilayer showed a significant improvement in the dielectric constant with respect to the pristine multilayer of PVDF.